Journal of Human Sport and Exercise - 2021 - Winter Conferences of Sports Science 2021
DOI: 10.14198/jhse.2021.16.proc3.28
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an extracurricular outdoor physical activity program on long-term memory in adolescent during COVID-19 pandemic

Abstract: The present study examined the effects of an 8-week extracurricular outdoor physical activity program aimed to improve long-term memory performance in adolescent concerning the Covid-19 period. Participants were 40 schoolchildren (aged 16-17) who trained twice a week in aerobic exercise two hours per session, randomly assigned to participate in either an extracurricular outdoor physical activity program (EG; n = 20) or a waitlist control group (CG; n = 20). At baseline and after training we administered the Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…To ensure the effectiveness of a Zumba training program, it is essential to tailor it according to the appropriate level of exercise intensity. Aerobic exercise has a positive and significant impact on lifestyle, as suggested by this study (Latino et al, 2021).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…To ensure the effectiveness of a Zumba training program, it is essential to tailor it according to the appropriate level of exercise intensity. Aerobic exercise has a positive and significant impact on lifestyle, as suggested by this study (Latino et al, 2021).…”
Section: Discussionsupporting
confidence: 59%
“…Thus, to expand knowledge in this field, the objective of this study was to evaluate the long-term effects of a Zumba physical activity program on the outdoor fitness of young women during the transition from the COVID-19 pandemic to the "new normal." This research aimed to explore the cognitive benefits of Zumba as a positive avenue for enhancing academic performance, especially considering the mandatory periods of rest imposed on adolescents due to the COVID-19 restrictions (Latino et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While the simple physical exercise given in this study required the students to simply remember the previously acquired information and relate it to the next movement and task, the repetitions of movements were more important than the ability to involve in-depth cognitive functions [42,43]. Several researchers claim that certain cognitive processes such as memory, attention, psychomotor, and visual-perceptual factors, all domains that could be affected by physical activity with cognitively engaging tasks, play a crucial role in the origin of a child's difficulties in the mathematical field [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Teacher-student relationships play a significant role in the quality of teaching and learning at school [1,2], especially when they are facilitated by the natural environment [3]. Indeed, several recent studies confirmed the presence of direct and indirect links between teacher-student relationships and student performance in several school subjects [4,5], their emotions [6] and even their social behaviors [7].…”
Section: Introductionmentioning
confidence: 99%